Chapter 10 Actor-networks, conservation treaties, and international environmental history - De Bont, Raf; Schleper, Simone (Taylor & Francis, 2024)
The Routledge Handbook of Environmental History presents a cutting-edge overview of the dynamic and ever-expanding field of environmental history. It addresses recent transformations in the field and responses to shifting scholarly, political, and environmental landscapes. The handbook fully and critically engages with recent exciting changes, contextualizes them within longer-term shifts in the field, and charts potential new directions for study. It focuses on five key areas: Theories and concepts related to changing considerations of social justice, including postcolonial, antiracist, and feminist approaches, and the field’s growing emphasis on multiple human voices and agencies. The roles of non-humans and the more-than-human in the telling of environmental histories, from animals and plants to insects as vectors of disease and the influences of water and ice, the changing theoretical approaches and the influence of concepts in related areas such as animal and discard studies. How changes in theories and concepts are shaping methods in environmental history and shifting approaches to traditional sources like archives and oral histories as well as experiments by practitioners with new methods and sources. Responses to a range of current complex problems, such as climate change, and how environmental historians can best help mitigate and resolve these problems. Diverse ways in which environmental historians disseminate their research within and beyond academia, including new modes of research dissemination, teaching, and engagements with stakeholders and the policy arena. This is an important resource for environmental historians, researchers and students in the related fields of political ecology, environmental studies, natural resources management and environmental planning. Chapters 9, 10 and 26 of this book are freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.